EVALUATION OF TRENDS IN FOREIGN TRADE DEVELOPMENT IN THE POST-COMMUNIST COUNTRIES OF EUROPE IN THE YEARS 2000–2012 FOLLOWING THEIR ACCESSION TO THE EU - Cieślik, Ewa; Biegańska, Jadwiga; Środa-Murawska, Stefania (Quaestiones Geographicae, 2016)
This paper seeks to analyse directions in foreign trade in the post communist countries of Europe over the years 2000–2012 in the context of changes observed in other EU states. It was assumed that changes in the directions of foreign trade in post-communist states would be similar to those noted in Western Europe. On the basis of data derived from the OECD, EUROSTAT and OECD-WTO we show that the trading rules used by the old EU-15 adopted by those countries have brought them measurable benefits. As a result, the post-communist economies have become similar to those of the EU-15. Considering the structure of their trade and links with the EU-15, it is apparent that they have become the main trading and investment partners for the European Union. Hence, their integration with the EU structures made their development faster, but also made them more sensitive to industrial and demand shocks coming from the eurozone. It is predicted that the present model is not going to change, especially in the context of the participation in production networks.